On the Classification of Almost Kenmotsu Manifolds of Dimension 3. (29th January 2013) - Wang, Yaning; Liu, Ximin
Abstract : This paper deals with the classification of a 3-dimensional almost Kenmotsu manifold satisfying certain geometric conditions. Moreover, by applying our main classification theorem, we obtain some suffcient conditions for an almost Kenmotsu manifold of dimension 3 to be an Einstein-Weyl manifold.